Pengaruh Pengawasan Pajak dan Pemeriksaan Pajak terhadap Penerimaan Pajak dengan Kepatuhan Wajib Pajak sebagai Variabel Intervening pada KPP Pratama Cilegon - Afe, Bayu Ryantoro; Lestari, Etty Puji; Gunawan, Diah Setyorini (Attractive : Innovative Education Journal, 2022)
Tax revenue and taxpayer compliance are topics of concern to the government, practitioners and academics today. The reason is, there are still many people in Indonesia who have negative thoughts about taxes. Optimization of the tax system will determine the extent to which the government is able to achieve the overall development target. This study aims to analyze the effect of tax oversight and tax audit on tax revenues with taxpayer compliance as an intervening variable at KPP Pratama Cilegon. This research will provide implications for the government in determining effective policy directions in collecting state revenues. The object of the study of this discussion is KPP Pratama Cilegon from 2017 to 2021. The type of study of this discussion is quantitative research. The sample used is 60 data using secondary data. The technique of determining the sample using purposive sampling. The analysis technique used in this study is Path Analysis. The results showed that supervision had a positive and significant effect on tax revenues, tax audits had a positive and insignificant effect on tax revenues, while taxpayer compliance was not able to mediate the effect of tax oversight and tax audits on tax revenues. Key words: Tax Supervision, Tax Audit, Taxpayer Compliance, Tax Revenue